Abdominal obesity diagnostics in clinical practice - E. N. Vorobyeva; I. V. Osipova; N. G. Veselovskaya; N. I. Mordvinova; R. I. Vorobyev (Кардиоваскулярная терапия и профилактика)
According to the WHO, there are 2 bilUon of obese people worldwide. Obesity prevalence is increasing in developed countries, and also tends to increase in developing regions. Some researchers have demonstrated that abdominal obesity (АО), and not general obesity with increased body mass index (MBI), is associated with raised cardiovascular risk. АО is diagnosed by computed tomography and anthropometry: measurement of waist circumference, waist/hips circumference ratio, sagittal abdominal diameter (SAD). SAD is linked to coronary risk and insulin resistance; therefore, is can be used for identifying obese patients with high risk of type 2 diabetes mellitus and coronary heart disease.